Targeting the Pseudomonas aeruginosa Virulence Factor Phospholipase C With Engineered Liposomes - Wolfmeier, Heidi; Wardell, Samuel J. T.; Liu, Leo T.; Falsafi, Reza; Draeger, Annette; Babiychuk, Eduard B.; Pletzer, Daniel; Hancock, Robert E. W. (Frontiers in Microbiology, 2022)
Engineered liposomes composed of the naturally occurring lipids sphingomyelin (Sm) and cholesterol (Ch) have been demonstrated to efficiently neutralize toxins secreted by Gram-positive bacteria such as Streptococcus pneumoniae and Staphylococcus aureus. Here, we hypothesized that liposomes are capable of neutralizing cytolytic virulence factors secreted by the Gram-negative pathogen Pseudomonas aeruginosa. We used the highly virulent cystic fibrosis P. aeruginosa Liverpool Epidemic Strain LESB58 and showed that sphingomyelin (Sm) and a combination of sphingomyelin with cholesterol (Ch:Sm; 66 mol/% Ch, 34 mol/% Sm) liposomes reduced lysis of human bronchial and red blood cells upon challenge with the Pseudomonas secretome. Mass spectrometry of liposome-sequestered Pseudomonas proteins identified the virulence-promoting hemolytic phospholipase C (PlcH) as having been neutralized. P. aeruginosa supernatants incubated with liposomes demonstrated reduced PlcH activity as assessed by the p-nitrophenylphosphorylcholine (NPPC) assay. Testing the in vivo efficacy of the liposomes in a murine cutaneous abscess model revealed that Sm and Ch:Sm, as single dose treatments, attenuated dermonecrosis by >30%; demonstrating a similar effect to that of a mutant lacking plcH in this infection model. Thus, sphingomyelin-containing liposome therapy offers an interesting approach to treat and reduce virulence of complex infections caused by P. aeruginosa and potentially other Gram-negative pathogens expressing PlcH.